Il postino Postman - Radford, Michael, 1946-; Cecchi Gori, Mario; Cecchi Gori, Vittorio; Noiret, Philippe; Troisi, Massimo, 1953-1994.; Cucinotta, Maria Grazia; Neruda, Pablo, 1904-1973.; t; Miramax Films ([Calif.] : Miramax Home Entertainment ; Burbank, Calif. : Distributed by Buena Vista Home Video, 1995)
A postman uses the poetry of Pablo Neruda to capture the heart of the woman of his dreams.
Philippe Noiret, Massimo Troisi, Maria Grazia Cucinotta.
Released as a motion picture 1995.
Based on the novel: Il postino, by Pablo Neruda; taken from Ardiente paciencia by Antonio Skarmeta.
Director of photography, Franco Di Giacomo; editor, Roberto Perpignani; music by Luis Enrique Bacalov.
Italian language; English subtitles.
Keywords: Neruda, Pablo, -- 1904-1973 -- Poetry -- Drama; Love in motion pictures; Comedy films -- Italy; Feature films -- Italy; Italian language -- Films for English speakers; Video recordings for hard of hearing people